As dificuldades da prática docente sobre gênero e sexualidade na escola - ALHO, Francimary Teles (2021)
The present Course Conclusion Paper - TCC discusses the theme “The Difficulties of Teaching Practice on Gender and Sexuality in School”. Having as main objective to analyze how the teachers of the Municipal School of Early Childhood Education and Elementary School Professor Maria Antônia de Paiva which is located in the municipality of Acará at Rua Luiz Miranda, number 629, with Travessa Ernesto Geisel, Bairro Cacoal in the municipality of Acará. The school has been working with the theme gender and sexuality, seeking to identify why this theme is not part of the pedagogical practice of the teachers of the school mentioned above. The proposal is that the topic under discussion becomes part of the school's daily life. It was through a bibliographic survey and then listening to some educators that it was possible to make the data collection performed through interviews, as well as observing the daily life of the school. It was a research of empirical and bibliographical nature, which incorporated besides theoretical references related to the subject, observations of the practices of teachers in the classroom as well as the relationship between the educators and the students. The work is organized in five sections where the topic under discussion is addressed. As results we can say that the school in question is still far from the discussion about gender and sexuality that can actually help children build a sexual identity. Religious precepts are still very strong in teachers' lives and practices, which leads to a conservative taboo practice when it comes to sexuality. This work is based on the collaboration of some authors such as: Falabelo (2005), Felipe (2007, 2012), Daughter (2012), Frison (2008), Moreira (2003) among others.